KINERJA IMPLEMENTASI PROGRAM KARTU INDONESIA SEHAT (KIS) DI KECAMATAN UJUNGJAYA KABUPATEN SUMEDANG - Rivaldi, Akmal Muhamad Rizki (LPPM UNSAP & FISIP UNSAP, 2025)
This study aims to determine the performance of the implementation of the Healthy Indonesia Card Program (KIS) in Ujungjaya District, Sumedang Regency. The research method used in this study is a qualitative research method. The informant determination technique is purposive sampling. With informants, namely the District Secretary, Head of Social Section, Head of Service Section, Social Staff, Service Staff. The data collection technique used is literature study and field study consisting of observation, interviews, documentation, and triangulation. The data validity technique used is credibility, transferability, dependability, and confirmability tests. While the data analysis technique in this study is Data Collection, Data Reduction, Data Display and Verification. Based on the results of the study, it was concluded that the performance of the implementation of the KIS Program in Ujungjaya District was not yet optimal. Several problems found include inaccurate target recipients, limited human resources, lack of facilities and infrastructure, and weak socialization and coordination between agencies. Efforts made to overcome these obstacles include increasing the capacity of implementing officers, updating recipient data, and strengthening cross-sector comnnication.